A review of anticancer, antitumor, and antioxidant of clinacanthus nutans - Zakaria, Khairun Najwa; Amid, Azura; Jamal, Parveen (Institute of Research Management and Consultancy University of Malaya and Malaysian Society for Molecular Biology and Biotechnology, 2017)
Clinacanthus nutans (CN) often use as herbal remedies complementary. The extracts from its dried leaves have been used traditionally to treat disease such as anti-venom for a snake / insect bite and reduce mild fever. A literature search showed that the ethanol extract of CN demonstrated an antioxidant activity and exhibited a protective effect against free radical. Experimental evidence confirmed that CN extract is used in treating tumor and cancer since it showed anticancer and anti-proliferative properties in vitro and in vivo. CN bioactive compounds demonstrated cytotoxic, anti-proliferative and antioxidant properties against cultured cancer cell lines, suggesting that CN is a suitable alternative for cancer prevention or treatment. CN is a good subject to be studied in the anticancer discovery area and hold great potential for being exploited as a chemopreventive drug since it possesses encouraging results with all the in vivo and in vitro tests carried out by many researchers